2008
DOI: 10.1080/09537100801947426
|View full text |Cite
|
Sign up to set email alerts
|

The effects of autologous platelet gel on inflammatory cytokine response in human peripheral blood mononuclear cells

Abstract: The potential therapeutic value and versatility of platelet-derived products has recently stimulated the research and interest in the field of regenerative medicine. Platelet gels (PG), generated by thrombin-activated platelets, represent a new biotechnology for stimulation and acceleration of tissue healing and regeneration. However, despite the diffused and successful use of PG in clinical practice, a more detailed knowledge of the cellular and molecular mechanisms involved is required. In the present study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 27 publications
2
13
0
Order By: Relevance
“…This discrepancy might be because of their use of monoclonal anti-CD3/anti-CD28 as a stimulus, which is likely to be much stronger than the more physiological antigenic stimuli used in this study. Using thrombin-generated platelet gels, Naldini et al showed that platelets reduced the release of IFN-g by LPS-stimulated PBMCs (8,38), and supporting their data, we did find a tendency toward platelet-mediated inhibition of TTinduced IFN-g production (Fig. 1B).…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…This discrepancy might be because of their use of monoclonal anti-CD3/anti-CD28 as a stimulus, which is likely to be much stronger than the more physiological antigenic stimuli used in this study. Using thrombin-generated platelet gels, Naldini et al showed that platelets reduced the release of IFN-g by LPS-stimulated PBMCs (8,38), and supporting their data, we did find a tendency toward platelet-mediated inhibition of TTinduced IFN-g production (Fig. 1B).…”
Section: Discussionsupporting
confidence: 74%
“…We therefore propose that the inhibitory effect of activated platelets on CD4 + T cell proliferation is directly related to their inhibition of TNF-a, in accordance with findings of Brown et al (37). Unlike other investigators (8,17), we found no effect of platelets on the T cell production of TNF-a, IL-10, IFN-g, IL-2, or IL-4. In particular, platelets influenced neither the frequency of IL-10-secreting CD4 + T cells nor the IL-10 production per individual cell, which disagrees with Gerdes and colleagues (17), who found that platelets enhanced IL-10 production by CD4 + T cells.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…These differences are likely the result of different methods of assessment (e.g., whole blood versus isolated cells; stimulated versus unstimulated cytokine production) and the degree of control of confounding factors (e.g., activity levels, light exposure, food intake). In this study, we used isolated PBMCs to prevent an influence of RBCs and platelets on the levels of cytokines released (45,46,54,55), and we studied cytokine secretion in stimulated cells (using both absolute levels and levels/cell). Under these conditions, the change in the timing of sleep from a day-oriented to a night-oriented schedule did not result in overall changes in the rhythm of immune cell counts or in the amounts of cytokines released with or without stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Although we could not eliminate the PBMC-bound platelets, the relative proportion of free platelets was always low (#3.9% of total cell number included in the platelet gate and the PBMC gate) and stable over time. This showed that our thorough washing procedure minimized the presence of platelets in the samples, making it unlikely that cytokine secretion was affected by their presence (45,46). p values , 0.05 were considered significant.…”
Section: Surface Staining Of Monocytes T Lymphocytes and Plateletsmentioning
confidence: 99%